Breaking the Silence: The Strange Case of an Eco-Cosmopolitan Chicana Detective - Pérez-Ramos, M.Isabel (International Journal of English Studies, 2022)
This article analyzes the strange eco-cosmopolitan detective attributes of Ivon, the protagonist in Alicia Gaspar de Alba’s 2005 novel Desert Blood: The Juárez Murders. Through this willful, queer, and feminist mestiza character, who continually trespasses and transgresses cultural borders, Gaspar de Alba challenges the standards of crime fiction in numerous ways, as argued in this paper. Moreover, she also manages to expose the transnational dimension of the exploitation, mistreatment, and even murder of women in Ciudad Juárez. Simultaneously, Ivon’s eco-cosmopolitanism acknowledges how the expendability thinking of free trade that partly sanctions the murder of women, also results in the environmental degradation of, and the free flow of toxins and pollution in the border. Ultimately, Ivon’s strange, eco-cosmopolitan investigative traits, serve as the tools to break the silence and start confronting the feminicides in Ciudad Juárez as well as the socio-environmental exploitation of the US-Mexico border region, fostering a positive socio-environmental change.